The economic recovery in the Central and Eastern European EU countries - GURGU, Elena (Annals of Spiru Haret University. Economic Series, 2011)
Following the recession in 2008-09, the economies of the eight EU countries in central and Eastern Europe outside the euro area (CEE) are recovering gradually, albeit with significant differences across countries. The expansion in economic activity is currently being driven primarily by exports as domestic demand remains subdued. Those countries that accumulated relatively more substantial internal and external imbalances before the financial crisis suffered more severe contractions in output during the crisis, and most of them face a more sluggish economic recovery.